International Price Differences in Ski Lift Tickets - Martin Falk (Swiss Journal of Economics and Statistics, 2011)
This paper provides empirical evidence on international price differences in ski lift tickets based on 214 ski areas in Austria, France, and Switzerland for the winter season 2010/2011. We find that French and Austrian one-day lift tickets (net of VAT) are an average of 17 and 7 per cent lower, respectively, than Swiss ticket prices after controlling for ski areas' characteristics. The results of quantile regressions show that the magnitude of the international price differences is quite similar for low- and high-priced ski areas. Furthermore, price differences across countries do not increase with distance to the nearest border ski area.
Keywords: D40; F3; L83; L11; 330; International price differences; ski areas; quality characteristics; quantile regressions